The Determinants Of Integrated Reporting Adoption In Manufacturing Companies In Indonesia - Dinaroe Dinaroe; Shabrina Shabrina; Riantari Maharani; Cut Darmawati (Science and Education Journal (SICEDU), 2026)
This study investigates whether board characteristics, institutional ownership, and audit committee activity influence the adoption of integrated reporting among manufacturing companies listed on the Indonesia Stock Exchange. Firm size and profitability are included as control variables. The study retains its original quantitative design and uses secondary data from the annual reports of manufacturing companies for the 2018-2020 period. A purposive sampling procedure generated 171 firm-year observations, and the hypotheses were tested using multiple linear regression. Integrated reporting adoption was measured through a content-analysis index based on the content elements of the International Integrated Reporting Framework. The findings show that board activity and firm size have positive and statistically significant effects on integrated reporting adoption. By contrast, board size, board independence, board diversity, institutional ownership, audit committee, and profitability do not show significant effects. These findings suggest that, in the Indonesian manufacturing context, the frequency of board deliberation and organizational resource capacity are more decisive for integrated reporting adoption than formal board composition or ownership concentration. The study contributes to the literature by providing empirical evidence from an emerging market during the pre-ISSB sustainability disclosure era and offers a baseline for assessing how Indonesian listed companies may respond to the subsequent development of sustainability disclosure standards.